Microsatellite markers as a tool to study reproductive success in the Pacific oyster, Crassostrea gigas (Thunberg), under controlled hatchery conditions - Boudry, Pierre; Collet, Bertrand; Cornette, Florence; Hervouet, Veronique; Bonhomme, Francois (92nd Annual Meeting of the National Shellfisheries Association, 2000)
Oysters, like many marine species have a very high fecundity. Previous studies have shown that populations, from both hatcheries and the natural environment, have very low Ne/N ratios. These observations reveal high variation in reproductive success. In order to study individual reproductive success under controlled conditions, we used microsatellite markers to quantify parental contributions in in vitro crosses (5 males and 5 females) of Crassostrea gigas, the Pacific oyster. High polymorphism of the microsatellites (more that 50 alleles per locus) eased the parentage identifications. The results of a cross allowing gametic competition were compared with the results from a second cross where the gametes of the same parents were kept separate for each parental combination until after fertilization. The progeny were then sampled at three stages of development and the parental contributions determined to follow their evolution through time. Despite the fact that equal numbers of gametes were mixed for each male and each female, the contributions of these parents to the resulting progeny was highly unbalanced at both larval and juvenile stages in both crosses. We demonstrated that variation in individual reproductive success is due to both spermatic competition and selective phenomena at early stages.